The official client/server computing guide to Data Warehousing - Gill, Harjinder S. (Que Corp., 1996)
Data warehouses are quickly becoming an important element of a total IS solution. This book clearly explains the business benefits and pitfalls of implementing a data warehouse. Includes a data warehouse planning tool for building the warehouse architecture and evaluating software vendors.